Risk of depression in patients with inflammatory bowel disease - Geiß, Thomas; Berens, Sabrina; Hoffmann, Peter; Gauss, Annika (Journal of digestive diseases, 2018)
OBJECTIVE Depression is more prevalent in patients with inflammatory bowel disease (IBD) than in the general population. This study evaluated disease-related risk factors for depression in Crohn's disease (CD) and ulcerative colitis (UC). METHODS Altogether 348 patients with IBD (228 with CD, 120 with UC) were included at our Outpatient IBD Clinic. Their characteristics, laboratory results and scores of depression, quality of life and clinical disease activity were retrospectively retrieved from questionnaires and medical records. The patient health questionnaire 9 (PHQ-9) was used as an algorithm for a probable diagnosis of major depression employing a cut-off point ≥10. Logistic regression analyses were performed to identify risk factors for depression. RESULTS Among these patients, 163 (46.8%) had no or minimal depression (PHQ-9 score 0-4), 108 (31.0%) had mild depression (PHQ-9 score 5-9) and 77 (22.1%) were at risk of major depression (PHQ-9 score ≥10). Patients with CD had a higher risk of major depression than those with UC (25.4% vs 15.8%, P = 0.040). PHQ-9 scores correlated strongly with clinical disease activity and quality of life scores in both groups but only weakly and solely in the CD group with biochemical disease activity. Clinical disease activity was identified as the only independent risk factor for depression in CD (odds ratio 7.814, 95% CI 2.688-22.717, P < 0.001), while no independent risk factor for depression was detected in UC. CONCLUSION Achieving clinical remission in patients with IBD seems to be the most important factor to reduce the risk of depression.
Gesehen am 11.12.2019